Melorheostosis of the hand affecting the c6 sclerotome and presenting with carpal tunnel syndrome - Abdullah, Shalimar (Singapore Med J, 2014)
Melorheostosis is a rare, progressive bone disease accompanied by hyperostosis and soft tissue fibrosis. While affected adults present with contracture and pain, children present with limb length discrepancy and deformity. We report the case of a 20-year-old woman with melorheostosis since childhood who presented with right hand deformity and numbness. Radiographs showed not only a combination of dense sclerosis and opacities, but also the classic ‘flowing candle wax’ appearance. Radiography can be used to identify melorheostosis, thus preventing unnecessary bone biopsies. Carpal tunnel release revealed the presence of a thickened flexor retinaculum and a degenerated median nerve distal to the retinaculum, but did not show hyperostosis. This case highlights the role of nerve decompression in melorheostosis and the importance of early identification of the disease to prevent unnecessary bone biopsies.